Improving Islamic Education Learning Outcomes through the Problem Based Learning Model at State Senior High School 13 Padang - Hendri, Osmi (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic education learning using the Problem based learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were senior high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure the improvement of student learning outcomes in Islamic education learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the Problem based learning model can improve student learning outcomes in Islamic education learning. This can be seen from the increase in the percentage of completeness of improving student learning outcomes in each cycle with details of the pre-cycle 44.56%, the first cycle 67.47% and in the second cycle increased to 89.57%. Thus, the use of Problem based learning model can be used as an alternative to increase student activity in Islamic education learning in Islamic education learning.